CAUSATIVE CONSTRUCTION OF ACEH LANGUAGE: TYPOLOGY APPROACH - Neni Umar; Mulyadi Mulyadi; Nurlela Nurlela (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
This study discusses causative construction in Acehnese language typologically. The problems studied were (1) the type of causative construction of the Aceh language typologically, (2) the relationship of the causative construction of Aceh language in typology, and (3) structures that establish the causative construction of Acehnese language. Research data, both oral and written, were obtained by speaking and listening methods. All data are examined by the identity and distributional methods. The results of the study showed that typologically the causative construction of Aceh language consists of morphological causative, lexical causative and analytic causative. Aceh language causative construction in this paper is investigated through parameters of semantics and formal. This construction was produced by combination of clause and conjunction ‘kerna’ or ‘seubap’; using analytical causative verb ‘peugot’ and ‘geuyu’; morphological causative affixes ‘meu-‘, ‘peu-‘ and ‘seu-‘; and using certain lexical causative in which have causative meaning. The relationship of the causative construction of the Aceh language in a syntactic typology, namely causative morphology and lexical causative was included in the causative construction of monoclauses, whereas analytic causative was included in the causative construction of biclauses. Structurally, testing is done by pinning syntactic operations, hence causative analytic was formed by biclauses structures, while lexical and morphological causative was formed by monoclausal structures.